Vaginal-perineal cultures for detecting group B streptococci and extended spectrum β-lactamase producing bacteria in pregnancy. (October 2019) - Huang, Dorothy J.; Hösli, Irene; Tschudin-Sutter, Sarah; Pfister, Tabea; Granado, Christina; Müller-Borer, Doris; Schötzau, Andreas; Frei, Reno; Dangel, Marc; Huhn, Evelyn A.; Widmer, Andreas; Vuichard-Gysin, Danielle
Abstract: Objective: To compare the detection rates of vaginal-perineal cultures for group B streptococci (GBS) with the standard vaginal and rectal cultures and evaluate the diagnostic yield of vaginal-perineal vs. rectal swabs for extended spectrum β-lactamase producing Enterobacterales (ESBL-E) during the third trimester of pregnancy. Study design: Vagino-perineal and rectal swabs were collected cross-sectionally from pregnant women between 35–37 weeks gestation and tested for the presence of GBS and ESBL-E. Accuracy of the vagino-perineal swab was compared to the combined vagino-perineal/rectal swab. Risk factors for ESBL carriage were examined. Degrees of pain, discomfort and stress related to the rectal swab were analyzed on visual analogue scales. Results: 48 out of 250 participants (19.2%) were GBS positive. The vagino-perineal swab was positive in 44 of 48 women (91.7%) yielding a negative predictive value of 98.1%. Agreement (kappa) between the two methods was 0.95. Six out of 190 women with additional ESBL-E screening (3.2%) tested positive by rectal swab. Of these, only two had also a positive vagino-perineal swab. The rectal swab caused overall little subjective discomfort, pain or stress, as indicated by low scores indicated on the visual scales. Conclusions: The GBS detection rate of the vagino-perineal swab was lower compared to the reference standard. However, agreement between the two screening methods was high and there were no cases of GBS neonatal sepsis in the recruited population, supporting this less invasive screening strategy. In contrast, the vaginal-perineal swab was inferior to the rectal swab for detecting ESBL-E, indicating that this less invasive method for detecting antibiotic resistant bacteria that may be potentially transferred to the neonate during labor and delivery would be inappropriate for ESBL-E screening in pregnant women. The low ESBL-E carriage rate among pregnant women likely reflects the prevalence in the general population.